Studi Kualitas Jasa Dan Pemasaran Relasional, Pengaruhnya Terhadap Kepuasan Dan Loyalitas Nasabah Bank Syariah Di Kota Makassar - Nuhung, Mahmud (Jurnal Ekonomi Balance, 2012)
Associated with existing theoretical review, this study aims to: (1) recognize and analyze the influence of service quality on customer satisfaction Islamic bank; (2) recognize and analyze the influence of service quality on customer loyalty Islamic bank; (3) recognize and analyze the influence of relational marketing to customer satisfaction Islamic bank; (4) recognize and analyze the influence of relational marketing on customer loyalty Islamic bank; (5) recognize and analyze the influence of customer satisfaction on customer loyalty Islamic bank.This study uses primary data. The population is Islamic bank customers in the city of Makassar. The sample of 300 respondents selected from 4 (four) of Islamic banks are selected purposively, that is (1) bank Muamalat, (2) bank BNI Syariah, (3) BTN Syariah, and (4) Bank Syariah Mandiri with Slovin formula then selected samples proportionally.By using analytical methods SEM (Structural Equation Model) results showed that: (1) service quality has positive and significant impact on customer satisfaction with loading factor 0.586 with probability 0.019; (2) service quality has no significant influence on customer loyalty Islamic bank; (3) relational marketing significantly influence customer satisfaction Islamic bank; (4) relational marketing no significant effect on customer loyalty; (5) customer satisfaction significantly influence customer loyalty.Keywords: service quality, relationship marketing, customer loyalty, customer satisfaction